Przemiany w polityce socjalnej w Republice Federalnej Niemiec - Zerche, Jürgen (Wydział Prawa i Administracji UAM, 1978)
The author tries to show basic transformations which have taken place within the period of 30 years of the Federal Republic of Germany. In the introductory part the author underlines fundamental provisions in the sphere of social policy included in the Constitution of the FRG, and then he tries to determine practical importance of social achievements. The changes are explained by such quantitative indicators like: sizes of pensions, sizes of nominal and real wages, total size of social services, unemployment benefits and so on. Along with many positive changes the author shows also weak points (shadows) of the social policy in the FRG. The shortcoming financial means for pensions and legal social insurance are reckoned among them. The author represents the opinion that the hitherto existing system of social ensuring old people as well as homeless people and ethnic minorities is far from the optimum. The author regards further reform of the social system leading to creation of a coherent concept of social policy is indispensable. According to the author this concept should be based on rationalistic and democratic-socialistic principles.
The Changes in Social Policy in the Federal Republic of Germany